Catch-22 [videorecording (DVD)] - Nichols, Mike; Henry, Buck; Arkin, Alan; Balsam, Martin, 1919-1996; Benjamin, Richard, 1938-; Heller, Joseph (Paramount, 2001)
The story of a group of fliers in the Mediterranean during World War II.